PENGEMBANGAN E-LKPD MATERI PERTUMBUHAN DAN PERKEMBANGAN BERORIENTASI PENDEKATAN DEEP LEARNING UNTUK MELATIH KOMPETENSI LITERASI SAINS - Salsabiila, Putri Aura; Rachmadiarti, Fida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aimed to produce a valid, practical, and effective e-LKPD (e-LKPD) based on a deep learning approach to stimulate students' scientific literacy skills. Using the Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate), this product was piloted on 32 eleventh-grade students of SMA Negeri 3 Surabaya. Data collection was conducted using validation techniques, practicality testing, and evaluation of scientific literacy learning outcomes. The results of the research analysis indicated excellent quality e-LKPD with a validity percentage of 98.6% (very valid). The practicality aspect of the product achieved a perfect response of 100% (very practical), while the effectiveness test proved that students' scientific literacy completion rate reached 93.75% (very effective). Based on the development test results, the Deep Learning-based e-LKPD on Growth and Development can be concluded as valid based on expert validation results, practical based on learning implementation and positive student responses, and effective based on students' achievement of learning completion and improvement in scientific literacy skills. Thus, the developed e-LKPD is suitable for use as a learning medium to practice scientific literacy skills and has the potential to enrich the reference list of interactive digital learning media to support improving the quality of biology learning at the high school level.